2011
DOI: 10.1016/j.bbrc.2011.09.106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of translocation of uracil–DNA glycosylase from Escherichia coli between distributed lesions

Abstract: Uracil-DNA glycosylase (Ung) is a DNA repair enzyme that excises uracil bases from DNA, where they appear through deamination of cytosine or incorporation from a cellular dUTP pool. DNA repair enzymes often use one-dimensional diffusion along DNA to accelerate target search; however, this mechanism remains poorly investigated mechanistically. We used oligonucleotide substrates containing two uracil residues in defined positions to characterize one-dimensional search of DNA by Escherichia coli Ung. Mg2+ ions su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
(49 reference statements)
1
15
1
Order By: Relevance
“…These experiments measure the rate at which a glycosylase cleaves consecutive damage sites within a single DNA strand of a duplex. The processivity of E. coli uracil DNA glycosylase (Udg) was examined using both plasmid [21] and linear DNA substrates [22–25]. Similar to what was observed for T4 endonuclease V, the processivity of Udg appears to be highly dependent on salt conditions for both substrates.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These experiments measure the rate at which a glycosylase cleaves consecutive damage sites within a single DNA strand of a duplex. The processivity of E. coli uracil DNA glycosylase (Udg) was examined using both plasmid [21] and linear DNA substrates [22–25]. Similar to what was observed for T4 endonuclease V, the processivity of Udg appears to be highly dependent on salt conditions for both substrates.…”
Section: Introductionmentioning
confidence: 94%
“…The presence of the EcoRI enzyme bound to the site between the lesions decreased the processivity of AAG by only 50%, indicating that some of the glycosylases were able to hop over the restriction enzyme to process the second lesion. In other studies, Udg was shown to be able to bypass both nicks and single-stranded gaps, albeit with reduced rates of correlated cleavage of uracils on the opposite side of the gap [25, 26]. In order to detect intersegmental transfer, Hedglin et al designed substrates consisting of two damaged oligos connected by a flexible PEG tether, increasing the local concentration of the two oligos while preventing sliding between them.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the sliding mechanism plays an essential function in Ura recognition by UNG since the probability of finding the damaged site by DNA hopping alone is low . In their study to characterize the one‐dimensional search of DNA by e UNG using the ODN‐based assay with ODN substrates that contained two uracil residues at defined positions Mechetin and Zharkov estimated a characteristic one‐dimensional search distance of ∼100 nucleotides and a translocation rate constant of ∼2 × 10 6 s −1 …”
Section: Introductionmentioning
confidence: 99%
“…The processive sliding mechanism has been tested using correlated cleavage experiments, and it does appear that several glycosylases are able to sequentially process closely spaced lesions. However, these assays are unable to directly observe long range interactions between the glycosylase and DNA, and they also are unable to characterize glycosylase interactions with undamaged DNA (Bennett et al, 1995; Dowd and Lloyd, 1990; Gruskin and Lloyd, 1988; Higley and Lloyd, 1993; Mechetin and Zharkov, 2011; Porecha and Stivers, 2008; Purmal et al, 1994; Sidorenko et al, 2008). …”
Section: The Target Search On Undamaged Dnamentioning
confidence: 99%